ANALISIS PENGARUH BUDAYA ORGANISASI, KOMPETENSI, DAN MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI PADA PDAM TIRTA BINANGUN KULONPROGO) - Vitria, Vita; Muttaqiyathun, Ani (Universitas Ahmad Dahlan, 2018)
This study aims to determine: (1) the influence of organizational culture, competence and motivation for the performance of PDAM Tirta Binangun's employees Kulonprogo Regency, (2) the influence of organizational culture on performance PDAM Tirta Binangun employees, Kulonprogo Regency, (3) influence competence in the performance of PDAM Tirta Binangun Regency employees Kulonrogo, (4) the influence of motivation on the performance of employees of PDAM Tirta Binangun Kulonprogo Regency. The sample in this study were employees of PDAM Tirta Binangun Kulonrogo Regency with a total of 60 employees with engineering leadership agency / institutional sample. Data collection using questionnaire while data analysis was performed using regression analysis linear multiple. Testing the validity in this study uses correlation product moment. Hypothesis testing using the F test and t test. At a significance level of 5%, the results of the study show that: (1) culture organization, competence and motivation simultaneously have influence significant effect on the performance of employees of PDAM Tirta Binangun Kulonprogo Regency is indicated by a sign count value of 0,000 <0.05. (2) organizational culture has a significant effect on the performance of employees of PDAM Tirta Binangun Kulonprogo Regency is indicated by the calculated sign value of 0.012 < 0.05. (3) competence has a significant effect on the performance of PDAM employees Tirta Binangun Kulonprogo Regency is indicated by the calculated sign value 0.022 <0.05. (4) motivation has a significant effect on employee performance PDAM Tirta Binangun Kulonprogo Regency is indicated by a sign value count 0.016 < 0.05.